Occupational health aspects of the arsenic extractive industry in Britain (1868-1925). Issue 9 (September 1988) - Harper, M
Abstract : A historical survey into the occupational hazards of mining and refining arsenic is presented together with the measures adopted for their control. The industry is placed in the social perspective of its time and it is suggested that this experience could be of value to those who may encounter similar problems where arsenic is extracted elsewhere in the world.